Psychological Distress in Cancer Patients with Underage Children - Akter, Jamila; Khan, Jaglul Gaffer; Khan, Manzurul Haque; Hossain, Mohammad Zaid (Journal of Dhaka Medical College, 2016)
Context: A cross-sectional comparative study was designed to compare psychological distress in cancer patients with and without minor children. Materials and methods: This study was done to compare anxiety and depression status among the cancer patients attending at National Institute of Cancer Research Hospital, Oncology department in Dhaka Medical College Hospital and in Uttara Adhunik Medical College Hospital. The study was conducted from September, 2012 to June, 2013. Respondents had been divided into two groups. In study group 123 cancer patients having underage children were included and in comparison group 116 cancer patients without having underage children were selected. Purposive sampling was applied. All the married cancer patients in both groups were selected randomly each between the age from 20 to 60 years with minimal or no physical difficulties. They did not have any history of prior psychiatric illness or co morbidities or substance abuse related to development of secondary psychiatric disorders. Distress among the patients were measured with the Hospital Anxiety and Depression Scale (Two sub scales A Anxiety subscale and D Depression subscale). Result: In the study group, 60.2% respondents were male and 39.8% female. And in comparison group male and female were 42.2% and 57.8%. Mean age of the participants in study group was 36.97±4.37 and in comparison group was 42.98±11.74 years. The mean duration since diagnosis was 12.85±13.11 months in study group and 11.53±6.72 months in comparison group. Majority of the respondents in study group were suffering from guynaecological cancer (25.2%) and gastro intestinal cancer (25.2%). Majority cancer in comparison group were guynaecological cancer (31%) and haematolymphoid cancer (20.7%) as well. Metastasis was present in 42.3% patients in study sample and 35.3% patients in comparison group. In study group 99.2% patients were suffering from both anxiety and depression. Majority (79.3%) patients in comparison group had been found depressed and 70.7% of them were anxious also. In study group 48.8% had moderate anxiety, 39% had severe and 11.4% had mild anxiety. Only 0.8% cancer patient had normal anxiety in this group. In comparison group 29.3% patients were normal in this regard. Majority (64.7%) had mild anxiety, 6% had moderate and no one had severe anxiety. Anxiety status was significantly different between the groups ( p < 0.001 ). Majority of the cancer patients in study group were suffering from depression. In this group 45.5% had moderate, 37.4% had severe, 16.3% had mild depression. In comparison group 62.1% had mild, 20.7% normal, 16.4% moderate and 0.9% had severe depression. The groups were significantly different ( p < 0.001 ) in depression status. In study group mean anxiety score in male was 15.72±2.314 and in female was 12.06±2.802, i.e. father with minor children were suffering from more anxiety than the mother (t = 7.878, p < 0.001). Mean depression score in male in study group was 11.91±2.489 and in female was 17.55±2.542, i.e. female cancer patients with minor children were found more depressed than male (t = 12.211; and p < 0.001). Conclusion: Almost all of the cancer patients with minor children had been found psychologically distressed. Cancer father with minor children were more prone to development of higher anxiety than the mothers in the same group. Female cancer patients with minor children were found more depressed than male. J Dhaka Medical College, Vol. 24, No.2, October, 2015, Page 146-151